The Potential of Greenhouse Gas (GHG) Emissions From Energy Consumption in Culinary MSME - Panjaitan, Kiki Pratiwi; Husin, Amir; Aththorick, T Alief (Tunas Geografi, 2024)
The Earth's surface temperature increases each year due to activities carried out by individuals or companies. Calculating the carbon footprint is one way to determine the emissions generated by human activities. Micro, Small, and Medium Enterprise (MSME) business operators have the potential to contribute to the carbon footprints originating from the use of Liquefied Petroleum Gas (LPG), fuel, and electricity. This research serves as a preliminary analysis to understand MSMEs' GHG emissions from energy and fuel use and identify appropriate strategies to reduce their carbon footprint using a standardized calculation method. This research uses a carbon footprint calculation method based on the methodology established by the Intergovernmental Panel on Climate Change. The analysis results show that the most significant emission sources from culinary MSME activities are restaurants, with approximately 3,079 CO2eq/year, followed by fried chicken at an average of 2,682 CO2eq/year, and meatball soup at around 2,504 CO2eq/year. The MSME with the highest income is fried chicken, with an average monthly revenue of IDR 19,225,000, while the lowest income is from siomay at IDR 7,700,000 per month. Income has an impact of 93.3% on the carbon footprints. Management measures that can be taken include analyzing which stages of the production process require significant energy, so strategies can be formulated to reduce the emissions produced. Additionally, the government should promote carbon-saving movements and educate the public about energy-efficient household appliances.